Monetary policy and the zero bound to interest rates: a review - Tony Yates (European Central Bank (ECB), 2002)
This paper reviews the literature on what the zero bound to nominal interest rates implies for the conduct of monetary policy. The aim is to evaluate the risks of hitting the zero bound; and to evaluate policies that are said to be able to reduce that risk, or policies that are proposed as means of helping the economy escape if it is in a zero bound 'trap'. I conclude that policies aimed at 'cure' are arguably more uncertain tools than those aimed at 'prevention', so prevention is a less risky strategy for policymakers. But since the risks of hitting the zero bound seem quite small anyway, and the risks of encountering a deflationary spiral smaller still, it is conceivable that inflation objectives that typify modern monetary regimes already have more than enough insurance built into them to deal with the zero bound problem.
Keywords: E52; E3; F41; 330; liquidity trap